Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Asset Pada Perusahaan Subsektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2023 - Nurpurnamasari, Herni; Dumilah, Ratna (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of Current Ratio and Debt To Equity Ratio on Return On Assets in mining sub-sector companies listed on the Indonesia Stock Exchange. The research method used in this study is a quantitative method with a descriptive approach. The population used is the financial statements of mining sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2023 period totaling 81 companies. The sample of this study was determined by a sampling technique using the purposive sampling method. In the mining sector with a total sample of 7 companies with a 6-year observation method so that 42 sample data were obtained. The analysis technique in this study uses descriptive statistics, classical assumption tests, multiple regression analysis and hypothesis testing using the E-views 12 program. The results of this study indicate that partially using the t-test, the Current Ratio variable has a significant effect on Return On Assets with a calculated t value greater than the t table (2.445800 > 2.021) and a significant value smaller than 0.05 (0.0191 <0.05) while the results of the Debt To Equity Ratio partially have a significant effect on Return On Assets with a calculated t value smaller than the t table (-2.065811 <2.021) and a significant value smaller than 0.05 (0.0455 <0.05). Current Ratio and Debt To Equity Ratio simultaneously affect Return On Asset with a calculated f value greater than F table (5.862975 > 3.238) and a significant value less than 0.05 (0.005940 < 0.05). The Contribution Determination Coefficient is 19.1735%, while the remaining 80.8265 is explained by variables not included in this research model